際際滷

際際滷Share a Scribd company logo
How to Multiply Binomials Using FOIL Method By: Scott Seman
The FOIL Method You must find the sum of the product of these terms F stands for the First terms O stands for the Outside terms I stands for the Inner terms L stands for the Last terms
First lets start with two binomials. (x+5)*(2x+2)
F OIL using ( x +5)*( 2x +2) For F, X is the first term of the 1st binomial and 2x is the first term of the 2nd binomial
Multiply F terms of ( x +5)*( 2x +2) X * 2x = 2x 族
F. O .I.L. using ( x +5)*(2x+ 2 ) For O, X is the outer term of the 1st binomial and 2 is the outer term of the 2nd binomial
Multiply O terms of ( x +5)*(2x+ 2 ) X * 2 = 2x
FO I L using (x+ 5 )*( 2x +2) For I, 5 is the inner term of the 1 st  binomial and 2x is the inner term of the 2 nd  binomial
Multiply I terms of (x+ 5 )*( 2x +2) 5 * 2x = 10x
FOI L  using (x+ 5 )*(2x+ 2 ) For L, 5 is the last term of the 1 st  binomial and 2 is the last term of the 2 nd  binomial
Multiply L terms of (x+ 5 )*(2x+ 2 ) 5 * 2 = 10
Add like terms to get answer F terms = 2x 族+ O terms =  2x + I terms =  10x+ L terms =  10 (x+5)*(2x+2)  = 2x族+12x+10

More Related Content

How to multiply binomials

  • 1. How to Multiply Binomials Using FOIL Method By: Scott Seman
  • 2. The FOIL Method You must find the sum of the product of these terms F stands for the First terms O stands for the Outside terms I stands for the Inner terms L stands for the Last terms
  • 3. First lets start with two binomials. (x+5)*(2x+2)
  • 4. F OIL using ( x +5)*( 2x +2) For F, X is the first term of the 1st binomial and 2x is the first term of the 2nd binomial
  • 5. Multiply F terms of ( x +5)*( 2x +2) X * 2x = 2x 族
  • 6. F. O .I.L. using ( x +5)*(2x+ 2 ) For O, X is the outer term of the 1st binomial and 2 is the outer term of the 2nd binomial
  • 7. Multiply O terms of ( x +5)*(2x+ 2 ) X * 2 = 2x
  • 8. FO I L using (x+ 5 )*( 2x +2) For I, 5 is the inner term of the 1 st binomial and 2x is the inner term of the 2 nd binomial
  • 9. Multiply I terms of (x+ 5 )*( 2x +2) 5 * 2x = 10x
  • 10. FOI L using (x+ 5 )*(2x+ 2 ) For L, 5 is the last term of the 1 st binomial and 2 is the last term of the 2 nd binomial
  • 11. Multiply L terms of (x+ 5 )*(2x+ 2 ) 5 * 2 = 10
  • 12. Add like terms to get answer F terms = 2x 族+ O terms = 2x + I terms = 10x+ L terms = 10 (x+5)*(2x+2) = 2x族+12x+10